Clinical, radiological, and genetic variation in pontocerebellar hypoplasia disorder and our clinical experience - Serap Bilge; Gülen Gül Mert; Özlem Hergüner; Duygu Özcanyüz; Sevcan Tuğ Bozdoğan; Ömer Kaya; Cengiz Havalı (BMC, 2022)
Abstract Pontocerebellar hypoplasia (PCH) constitutes a heterogeneous neurodegenerative/neurodevelopmental disorder of the pons and cerebellum with onset in the prenatal period. Our study aimed to present different clinical and radiological manifestations of our genetically diagnosed PCH patients. Method: Six patients were enrolled in this study from September 2018 to March 2021. All the clinical radiological and genetic investigations were done at Cukurova University Medical School. Results: Five children were diagnosed genetically and categorized under one of the types of PCH (type 10,7,11). Homozygous mutations in CLP1 In PCH type 10, TOE1 in PCH type 7, and TBC1D23 in PCH type 11 were respectively detected. Pateint with PCH type 11 and female patient with PCH type 7 could walk and speak few words. Male patient with PCH type 7 had disorder of sex development. Conclusion: According to our study, PCH is a rare neurodegenerative disease, although some types are static as PCH11 male gender and PCH7 female gender. Some clinical features are specific to a definite type. PCH7 express disorders of sex development most apparent in 46 XY. Some ethnic groups could express distinct subtypes. PCH10 is seen in the Turkish population. Radiological imaging is beneficial in pre-diagnosis; all the patients had different pons and cerebellar hypoplasia degrees. Genetic testing like whole exome sequencing -next-generation sequencing is essential in setting the definite diagnosis and determining the type/subtype of PCH.